Exploring the interior : essays on literary and cultural history - Guthke, Karl Siegfried, 1933- (Open Book Publishers, 2018)
"In this fascinating collection of essays Harvard Emeritus Professor Karl S. Guthke examines the ways in which, for European scholars and writers of the eighteenth and early nineteenth century, world-wide geographical exploration led to an exploration of the self. Guthke explains how in the age of Enlightenment and beyond intellectual developments were fuelled by excitement about what Ulrich Im Hof called "the grand opening-up of the wide world", especially of the interior of the non-European continents. This outward turn was complemented by a fascination with "the world within" as anthropology and ethnology focused on the humanity of the Indigenous populations of far-away lands - an interest in human nature that suggested a way for Europeans to understand themselves, encapsulated in Gauguin's Tahitian rumination "What are we?" The essays in the first half of the book discuss first- or second-hand, physical or mental encounters with the exotic lands and populations beyond the supposed cradle of civilisation. The works of literature and documents of cultural life featured in these essays bear testimony to the crossing not only of geographical, ethnological, and cultural borders but also of borders of a variety of intellectual activities and interests. The second section examines the growing interest in astronomy and the engagement with imagined worlds in the universe, again with a view to understanding homo sapiens, as compared now to the extra-terrestrials that were confidently assumed to exist. The final group of essays focuses on the exploration of the landscape of what was called "the universe within"; featuring, among a variety of other texts, Schiller's plays The Maid of Orleans and William Tell, these essays observe and analyse what Erich Heller termed "The Artist's Journey into the Interior." This collection, which travels from the interior of continents to the interior of the mind, is itself a set of explorations that revel in the discovery of what was half-hidden in language. Written by a scholar of international repute, it is eye-opening reading for all those with an interest in the literary and cultural history of (and since) the Enlightenment."--Publisher's website